Gender, ethnicity and sustainable mobility: a governmentality analysis of migrant Chinese women's daily trips in Sydney. Issue 1 (2nd January 2016) - Waitt, Gordon; Kerr, Sophie-May; Klocker, Natascha
Abstract: The automobile is acknowledged as an urgent environmental sustainability issue in cities where it remains pivotal to everyday life and society. We explore the potential of migrants – from societies where urban spaces and everyday life are not centred on the automobile – to elucidate pathways for reducing car dependence. This paper explores the sustainability implications of everyday mobility decisions in Sydney, Australia, through the mobility discourses of female migrants from China. Our governmentality analyses suggest a preference, among female Chinese migrants, to initially walk and cycle after arriving in Sydney. Many expressed a fear rather than a love of driving. For these migrant women, the decision to eventually purchase and use an automobile – in the specific transport context of Sydney – was forced rather than chosen. We call for others to address the reciprocal relationship between gender and ethnicity in their thinking about sustainable transport.